2021
DOI: 10.1016/j.numecd.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Are diabetes and its medications risk factors for the development of COVID-19? Data from a population-based study in Sicily

Abstract: Background and aims Diabetes mellitus (DM) has been associated with higher incidence of severe cases of COVID-19 in hospitalized patients, but it is unknown whether DM is a risk factor for the overall COVID-19 incidence. The aim of present study was to investigate whether there is an association of DM with COVID-19 prevalence and case fatality, and between different DM medications and risk for COVID-19 infection and death. Methods and Results retrospective observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 10 publications
(11 reference statements)
4
49
0
1
Order By: Relevance
“…There were 4,477 patients from 9 studies in this systematic review and meta-analysis [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ] [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ] [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ] [ Fig. 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 4,477 patients from 9 studies in this systematic review and meta-analysis [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ] [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ] [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ] [ Fig. 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dipeptidyl peptidase-4 inhibitor inhibitor exerts anti-inflammatory, anti-fibrotic, and anti-adipogenic properties, which may be useful in delaying the progression to hyper-inflammation in severe COVID-19 cases [ [4] , [5] , [6] ]. A multicenter study have shown that DPP-4 inhibitor was associated with lower mortality [ 7 ], while other studies did not [ 8 , 9 ]. This study aims to synthesize evidence on DPP-4 inhibitor and mortality in COVID-19 patients and factors affecting it.…”
Section: Introductionmentioning
confidence: 99%
“…After propensity score matching, the use of DPP4i was not associated with other adverse outcomes, such as need of ICU admission, mechanical ventilation, in-hospital complications, or long-time hospital stays [22]. A few other observational studies reported no association between DPP4i treatment and COVID-19-related mortality [23,24] or COVID-19 severity [25].…”
Section: Summary Of the Evidencementioning
confidence: 96%
“…Pre-existing diabetes, compared to those without has accounted for 24% vs. 10.2% in a report from China [7] ; 28.8% vs. 6.2% and 7.8% vs. 2.7% in multicenter studies from US [22] , and China [44] ; 24% vs. 20% in a meta-analysis [39] , and 10.6% vs. 2.1% in a South Korean population-based study [12] . While in Sicily, although diabetes was not a risk factor for COVID-19, it was associated with a higher fatality [45] .…”
Section: Discussionmentioning
confidence: 78%